Characters and Positive Traits in Selected Humorous Folktales of Sabah (Malay Literature, 2023)
The inheritance of traditional oral literature through the speech of individuals or storytellers is not just for entertainment, but also reflect the common sense of previous societies and possess the essence of teaching with the aim to provide education to the society. Nowadays, oral literature is documented, published and analyzed according to the needs of a study. Oral literature in the form of narrative, known as folktales, contains animal stories, humorous stories, tales and so on. Malay humorous folktales such as Pak Pandir, Lebai Malang and Si Luncai are so popular that their characters are often portrayed in a negative perspective, such as stupid, foolish and unlucky. This paper discusses ethnic humorous folktales from Brunei, Bajau Laut/Suluk and Dusun in Sabah. The data from this study were taken from Koleksi Cerita Rakyat Sabah (2019) compiled by Lokman Abdul Samad and Suhaimi Yasi, whereas data on Bruneian humorous folktales were obtained from fieldwork in 2012. Data analysis utilized the Theory of Emotional Intelligence by Salovey and Mayer (1990) to dissect characters and their characterization in the selected folktales. This study found that SabahFull text: PDF